2021
DOI: 10.5603/dk.2021.0020
|View full text |Cite
|
Sign up to set email alerts
|

Applying the health belief model and behavior of diabetic patients: A systematic review and meta-analysis

Abstract: The patient's belief and knowledge about his or her illness is the most important factor of disease control; the aim of present study is to perform a systematic review-based meta-analysis of health belief and its dimension's mean score in diabetic patients. The present systematic review and meta-analysis was conducted in 2020. Data were gathered by searching the google Scholar, Scopus, PubMed, Web of Science, and Science Direct databases from 2010 to 2020. Key words were "health belief", "hBM", "diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, theories, such as the Health Belief Model, were developed decades ago based on empirical evidence of the time. Since then, this model has been adapted to apply to noncommunicable and other infectious diseases [48,49]. Sadly, after decades of research using this model to understand HIV and AIDS, there is little evidence, as suggested by the current study, that anything is changing.…”
Section: Discussionmentioning
confidence: 96%
“…However, theories, such as the Health Belief Model, were developed decades ago based on empirical evidence of the time. Since then, this model has been adapted to apply to noncommunicable and other infectious diseases [48,49]. Sadly, after decades of research using this model to understand HIV and AIDS, there is little evidence, as suggested by the current study, that anything is changing.…”
Section: Discussionmentioning
confidence: 96%
“…According to Schwarzer, perceived benefits within the health performance process primarily operate during the motivation stage but exert a limited influence during the performance stage [ 48 ]. The health belief model, which relies on educational initiatives, the dissemination of relevant brochures and books, the conduct of face-to-face classes, the cultivation of personal and social motivation, and the bolstering of self-confidence, exerts a crucial impact on perceived benefits and cements its favourable position [ 21 , 57 ]. In a study by Farahmand et al ., lectures, question-and-answer sessions, group discussions, educational slides, and pertinent handouts were instrumental in enhancing subjects’ perception of “perceived benefits” [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, individuals must perceive a threat (comprising perceived susceptibility and severity) and believe that a particular behaviour leads to a desirable outcome at an acceptable cost to alter their current behaviour patterns successfully. Furthermore, they must feel empowered to overcome perceived obstacles during action [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The awareness scores of the respondents for various parameters were compared with the various demographic characteristics using Kruskal Wallis and chi-square tests (as the data was measured on an ordinal scale). Several studies (Wallace, 2002;Khosravizadeh et al, 2021) used HBM to recognise the respondents' perception of the susceptibility and seriousness of the disease which is used to explain the need to adopt some particular preventive behaviours. Similarly, SCT has also been used by some researchers for understanding physical activity health behaviours.…”
Section: Discussionmentioning
confidence: 99%